2020
DOI: 10.1016/j.celrep.2020.107631
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cell Fate Tracing Provides No Evidence for Mesenchymal to Epithelial Transition in Adult Fallopian Tube and Uterus

Abstract: SUMMARY The mesenchymal to epithelial transition (MET) is thought to be involved in the maintenance, repair, and carcinogenesis of the fallopian tube (oviduct) and uterine epithelium. However, conclusive evidence for the conversion of mesenchymal cells to epithelial cells in these organs is lacking. Using embryonal cell lineage tracing with reporters driven by mesenchymal cell marker genes of the female reproductive tract (AMHR2, CSPG4, and PDGFRβ), we show that these reporters are also expressed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…However, a recent cell fate tracing study found that the conclusive evidence for the conversion of mesenchymal cells to epithelial cells in adult uterine is lacking. The study of the embryonal cell lineage tracing with reporters driven by mesenchymal cell marker genes of the female reproductive tract (AMHR2, CSPG4, and PDGFRβ) showed that these reporters are also expressed in some oviductal and uterine epithelial cells at birth [ 110 ].…”
Section: Endometrial Epithelial Stem/progenitor Cellsmentioning
confidence: 99%
“…However, a recent cell fate tracing study found that the conclusive evidence for the conversion of mesenchymal cells to epithelial cells in adult uterine is lacking. The study of the embryonal cell lineage tracing with reporters driven by mesenchymal cell marker genes of the female reproductive tract (AMHR2, CSPG4, and PDGFRβ) showed that these reporters are also expressed in some oviductal and uterine epithelial cells at birth [ 110 ].…”
Section: Endometrial Epithelial Stem/progenitor Cellsmentioning
confidence: 99%
“…A comprehensive investigation into a role for MET in endometrial regeneration using a number of different lineage tracing mouse lines indicates that mesenchymal reporter-positive epithelial cells were identified at birth and maintained in adult epithelium, as expected for a mesodermal-derived epithelium. However, evidence of MET of adult mesenchymal cells, particularly during postpartum repair, was not identified suggesting that it is unlikely that the mesenchyme contributes to the adult epithelium (Ghosh et al, 2020).…”
Section: Role Of Endometrial Epithelial Stem/progenitor Cells In Re-epithelization and Post-partum Regenerationmentioning
confidence: 99%
“…Specific features of ECM composition and organization by SCs regulate their functional state through feedback mediated by integrin signaling and form a unique topography of connective tissue and determine its interaction with other cell types ( Mouw et al, 2014 ). Thus, properties of matrix produced by EndoSC can affect not only fibrogenesis but also angiogenesis and epithelialization, which are important for endometrial healing and provide an intriguing task for investigation of mechanisms in this field ( Fan et al, 2008 ; Owusu-Akyaw et al, 2019 ; Yin et al, 2019 ; Ghosh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%